Dynamic of Product Innovation, Community Involvement, and Regulatory Policy: Case Study of MSME Entrepreneurship in Indonesia - Chatra, Afdhal; Budaya, Indra; Saprudin, Saprudin; Judijanto, Loso (International Journal of Business, Law, and Education, 2024)
This research examines the dynamic interplay of product innovation, community involvement, and regulatory policies in the context of Micro, Small, and Medium Enterprises (MSMEs) entrepreneurship in Indonesia. MSMEs are pivotal contributors to Indonesia's economy, constituting a significant portion of the GDP and providing substantial employment. The study focuses on understanding how product innovation, community engagement, and regulatory frameworks influence the success of MSMEs. The research employs a conceptual framework, literature review, and empirical analysis to explore the relationships among these variables. Data collection involves structured surveys distributed among MSMEs, and the analysis employs Partial Least Squares Structural Equation Modeling (PLS SEM). The results indicate positive correlations between product innovation, community involvement, regulatory policies, and entrepreneurial success. The study's implications highlight the need for supportive regulatory environments, community-centric policies, and innovation support for MSMEs. The research contributes valuable insights for policymakers, industry stakeholders, and MSME entrepreneurs in Indonesia.